Selling and sales management. - Jobber, David, 1947-; Lancaster, Geoffrey, 1938-; Le Meunier-FitzHugh, Kenneth (Pearson Educational, 2025)
Over the past quarter of a century, Selling and Sales Management has proved itself to be the definitive text in this exciting and fast-paced subject area. This new edition comes fully updated with new case studies, using working businesses to connect sales theory to the practical implications of selling in a modern environment. It also contains the results from cutting-edge research that differentiates it from most of its competitors. The book continues to place emphasis on global aspects of selling and sales management.